Transthoracic echocardiography in patients with chronic kidney disease - Shrestha, Balaram; Gurung, Dhiraj; Dhungel, Sanjib (Journal of Kathmandu Medical College, 2019)
Background: Evaluation of cardiac diseases in chronic kidney disease has been rarely investigated in Nepal. Objectives: Objective of this study is to evaluate cardiac lesions in admitted chronic kidney disease patients. Methodology: It is a prospective observational study of echocardiography of chronic kidney disease patients from April, 2007 to April, 2013 in Nepal Medical College Teaching Hospital. Results: One hundred chronic kidney disease patients were evaluated. Male to Female ratio was 1.8:1 and age ± SD was 46.3 ± 17.2 years. Forty eight percent of the chronic kidney disease patients had left ventricular hypertrophy. Patients with chronic kidney disease with left ventricular hypertrophy group had interventricular septum of 1.5 ± 0.3 cm vs. 1.1 ± 0.1 cm (p<0.0001) and posterior wall of 1.1 ± 0.2cm vs. 1.0 ± 0.1cm (p< 0.01) in comparison to chronic kidney disease without left ventricular hypertrophy. Forty one percent had left ventricular systolic dysfunction with left ventricular ejection fraction of 39 ± 9.9 %. Pulmonary arterial hypertension was noticed in 39% patients. Valvular regurgitant lesions were quite common (241%) usually as multivalvular lesions (4.4 lesions per patient). Mitral regurgitation was the commonest regurgitant lesion (81%). Conclusion: Echocardiographic cardiac evaluation is useful to diagnose concomitant cardiac lesions for standard care of chronic kidney disease patients.